'Fame and Envy 2.0' in luxury fashion influencer marketing on Instagram: comparison between mega-celebrities and micro-celebrities. (8th April 2021) - Jin, S. Venus; Muqaddam, Aziz
This study addresses contemporary issues of online celebrities and the dynamics of fame and envy in Instagram influencer-based luxury fashion marketing from a consumer psychology perspective. A randomised between-subjects experiment ( N = 108) examined the influence of mainstream mega-celebrities versus Instagram micro-celebrities on various dimensions of consumer behaviour. The results indicate stronger main effects of Instagram micro-celebrities (versus mainstream mega-celebrities) on buying intention. Mediation analyses confirm the mediating effects of parasocial interaction and social presence on the relationship between celebrity types and buying intention. Results show moderating effects of materialism and envy in accounting for the effects of celebrity types on fashion marketing outcomes. This study provides marketing scholars with relevant theoretical explanations about consumer psychology of luxury and envy in social media marketing. With regards to managerial implications, current findings provide brand managers and advertising practitioners with empirical data about the efficacy of micro-celebrity practices in Instagram influencer marketing.